Promoting Vasa Vasorum Neovascularization of Vein Grafts Extenuates Hypoxia of the Wall and Its Subsequent Influence on Intimal Hyperplasia - Zou, Rong-Jiang (Chin Med J (Engl), 2017)
BACKGROUND: The autologous saphenous vein is the most common conduit for coronary artery bypass grafting, but the vein graft disease will occur. This study used Matrigel basement membrane matrix with many different growth factors to promote vasa vasorum neovascularization and extenuate the hypoxia to improve remodeling. METHODS: This study observed the hypoxia and thickness of the vein grafts at different times. Normal veins and vein grafts with 15 min of ischemia one day postoperatively were harvested in the neck of rabbits. Paired vein grafts with 15 min ischemia bilaterally (control vs. Matrigel basement membrane matrix) were performed and harvested at 2, 6, and 12 weeks postoperatively. The rabbits were randomly divided into four postoperative groups (six rabbits in each group): Group 1, one day postoperatively; Group 2, 2 weeks postoperatively; Group 3, 6 weeks postoperatively; and Group 4, 12 weeks postoperatively. The dimensions of vessel wall were captured, and the mean thicknesses of intima, media, and adventitia were measured. The hypoxia-inducible factor (HIF)-1α and HIF-2α labeling indices of intima, media, and adventitia were also measured. RESULTS: In Group 1, the labeling index of HIF-1α was high in the normal vein and decreased significantly in the vein graft one day postoperatively (intima: 80 ± 3% vs. 12 ± 1%, P = 0.01; media: 67 ± 5% vs. 11 ± 1%, P = 0.01; adventitia: 40 ± 10% vs. 7 ± 2%, P = 0.03). The labeling index of HIF-2α had similar trend as HIF-1α (intima: 80 ± 10% vs. 10 ± 5%, P = 0.02; media: 60 ± 14% vs. 12 ± 2%, P = 0.01; adventitia: 45 ± 20% vs. 10 ± 4%, P = 0.03). Compared with the control vein grafts, vein grafts with Matrigel basement membrane matrix had lower labeling indices of HIF-1α and HIF-2α in media and adventitia at Group 2 (HIF-1α: 34 ± 5% vs. 20 ± 4%, P = 0.04 for media; 23 ± 3% vs. 11 ± 2%, P = 0.03 for adventitia; HIF-2α: 37 ± 6% vs. 21 ± 4%, P = 0.03 for media; 24 ± 4% vs. 13 ± 2%, P = 0.04 for adventitia) and Group 3 (HIF-1α: 33 ± 4% vs. 7 ± 2%, P = 0.04 for media; 13 ± 3% vs. 3 ± 1%, P = 0.02 for adventitia; HIF-2α: 27 ± 4% vs. 12 ± 3%, P = 0.02 for media; 19 ± 2% vs. 6 ± 1%, P = 0.02 for adventitia). There were no differences in mean thickness of intima, media, and adventitia between bilateral vein grafts at 2, 6, and 12 weeks postoperatively. CONCLUSIONS: This study indicated that promoting vasa vasorum neovascularization of vein grafts extenuated hypoxia, but did not influence the intimal hyperplasia of the wall.